WEBVTT
00:00:02.800 --> 00:00:10.400
Consider the parametric curve π₯ is equal to one plus the sec of π and π¦ is equal to one plus the tan of π.
00:00:10.550 --> 00:00:16.670
Determine whether this curve is concave up, down, or neither at π is equal to π by six.
00:00:16.920 --> 00:00:23.980
The question gives us a curve defined by a pair of parametric equations π₯ is some function of π and π¦ is some function of π.
00:00:24.310 --> 00:00:29.680
We need to determine the concavity of this curve at the point where π is equal to π by six.
00:00:29.830 --> 00:00:32.810
Letβs start by recalling what we mean by the concavity of a curve.
00:00:33.050 --> 00:00:38.420
The concavity of a curve tells us whether the tangent lines to the curve lie above or below our curve.
00:00:38.650 --> 00:00:44.360
In particular, we can find this information by using the second derivative of π¦ with respect to π₯.
00:00:44.500 --> 00:00:49.530
We know if d two π¦ by dπ₯ squared is positive, then our curve is concave upward at this point.
00:00:49.580 --> 00:00:54.870
We also know if d two π¦ by dπ₯ squared is negative, then our curve is concave downward at this point.
00:00:55.140 --> 00:01:00.160
So, to find the concavity of our curve, we just need to find an expression for d two π¦ by dπ₯ squared.
00:01:00.190 --> 00:01:03.770
However, we canβt do this directly since weβre given a parametric curve.
00:01:04.040 --> 00:01:08.200
So, weβre going to need to recall some of our rules for differentiating parametric curves.
00:01:08.380 --> 00:01:12.650
First, we recall we can use the chain rule to find an expression for dπ¦ by dπ₯.
00:01:12.680 --> 00:01:20.920
If π¦ is a function of π and π₯ is a function of π, then dπ¦ by dπ₯ is equal to dπ¦ by dπ divided by dπ₯ by dπ.
00:01:21.180 --> 00:01:25.710
And this is only valid when the denominator dπ₯ by dπ is not equal to zero.
00:01:26.030 --> 00:01:29.330
But we want to find an expression for d two π¦ by dπ₯ squared.
00:01:29.330 --> 00:01:32.020
So, we need to differentiate this with respect to π₯.
00:01:32.160 --> 00:01:34.370
And we could do this again by using the chain rule.
00:01:34.530 --> 00:01:42.710
We would get that d two π¦ by dπ₯ squared is equal to the derivative of dπ¦ by dπ₯ with respect to π divided by dπ₯ by dπ.
00:01:42.960 --> 00:01:48.070
And of course, we still require our denominator dπ₯ by dπ is not equal to zero.
00:01:48.260 --> 00:01:54.200
So, to find an expression for d two π¦ by dπ₯ squared on our parametric curve, we need to find dπ¦ by dπ₯.
00:01:54.230 --> 00:01:57.810
Doing this, we need to find dπ¦ by dπ and dπ₯ by dπ.
00:01:58.040 --> 00:02:02.050
And π₯ and π¦ are already given as functions of π, so we can do this.
00:02:02.260 --> 00:02:04.400
Letβs start with finding dπ₯ by dπ.
00:02:04.430 --> 00:02:08.300
Thatβs the derivative of one plus the sec of π with respect to π.
00:02:08.580 --> 00:02:12.900
To do this, we recall one of our standard derivative results for trigonometric functions.
00:02:12.930 --> 00:02:19.690
The derivative of the sec of π with respect to π is equal to the sec of π times the tan of π.
00:02:20.060 --> 00:02:28.140
So, because the derivative of the constant one is equal to zero, we get dπ₯ by dπ is equal to the sec of π times the tan of π.
00:02:28.490 --> 00:02:31.800
We can now do the same to find an expression for dπ¦ by dπ.
00:02:31.860 --> 00:02:35.690
Thatβs the derivative of one plus the tan of π with respect to π.
00:02:35.970 --> 00:02:40.340
Once again, we need to use one of our standard derivative results for trigonometric functions.
00:02:40.370 --> 00:02:46.050
The derivative of the tan of π with respect to π is equal to the sec squared of π.
00:02:46.440 --> 00:02:50.860
So, this gives us that dπ¦ by dπ is equal to the sec squared of π.
00:02:51.120 --> 00:02:58.800
Now that we found expressions for dπ¦ by dπ and dπ₯ by dπ, we can use our formula to find an expression for dπ¦ by dπ₯.
00:02:59.130 --> 00:03:06.130
We get dπ¦ by dπ₯ is equal to the sec squared of π divided by the sec of π times the tan of π.
00:03:06.470 --> 00:03:12.110
Remember, to find d two π¦ by dπ₯ squared, we need to differentiate this expression with respect to π.
00:03:12.140 --> 00:03:15.490
So we should simplify this into a form which is easy to differentiate.
00:03:15.800 --> 00:03:20.930
To start, weβll cancel the shared factor of the sec of π in our numerator and our denominator.
00:03:21.230 --> 00:03:23.500
But this is still the quotient of two functions.
00:03:23.500 --> 00:03:25.860
We could differentiate this by using the quotient rule.
00:03:25.890 --> 00:03:28.680
However, we could simplify this to make it even easier.
00:03:28.950 --> 00:03:33.040
To help us simplify this, we need to recall two of our trigonometric identities.
00:03:33.070 --> 00:03:41.890
The sec of π is equivalent to one divided by the cos of π, and the tan of π is equivalent to the sin of π divided by the cos of π.
00:03:42.190 --> 00:03:51.480
Using our trigonometric identities, we get dπ¦ by dπ₯ is equal to one over the cos of π all divided by the sin of π divided by the cos of π.
00:03:51.790 --> 00:04:02.620
And either by using our rules for rearranging fractions or by multiplying the numerator and the denominator by the cos of π, we can just simplify this to get one divided by the sin of π.
00:04:02.940 --> 00:04:08.120
And, of course, we know that one divided by the sin of π is equivalent to the csc of π.
00:04:08.320 --> 00:04:15.250
And itβs important to note that this is a much easier function to differentiate than the sec of π divided by the tan of π.
00:04:15.640 --> 00:04:19.420
Weβre now almost ready to find our expression for d two π¦ by dπ₯ squared.
00:04:19.460 --> 00:04:21.880
Letβs start by finding an expression for our numerator.
00:04:21.940 --> 00:04:25.190
Thatβs the derivative of dπ¦ by dπ₯ with respect to π.
00:04:25.400 --> 00:04:29.160
And we already showed dπ¦ by dπ₯ is equal to the csc of π.
00:04:29.160 --> 00:04:32.810
So, we need to differentiate the csc of π with respect to π.
00:04:33.060 --> 00:04:35.660
And this is a standard trigonometric derivative result.
00:04:35.690 --> 00:04:43.790
We know the derivative of the csc of π with respect to π is equal to negative the cot of π times the csc of π.
00:04:44.140 --> 00:04:48.090
So, we found an expression for the numerator of d two π¦ by dπ₯ squared.
00:04:48.120 --> 00:04:51.850
We got negative the cot of π times the csc of π.
00:04:52.230 --> 00:04:55.620
Now, all we need to do is divide this by dπ₯ by dπ.
00:04:55.670 --> 00:04:57.530
And we already found dπ₯ by dπ.
00:04:57.560 --> 00:05:01.380
We got that this was equal to the sec of π times the tan of π.
00:05:01.620 --> 00:05:13.460
So, by using our formula, we get d two π¦ by dπ₯ squared is equal to negative the cot of π times the csc of π divided by the sec of π multiplied by the tan of π.
00:05:13.750 --> 00:05:16.370
Now, thereβs a few different ways we could proceed with this question.
00:05:16.430 --> 00:05:21.830
For example, we only need to find the concavity of our curve at the point where π is equal to π by six.
00:05:21.990 --> 00:05:25.870
So, at this point, we could just directly substitute this value into our expression.
00:05:25.940 --> 00:05:28.840
However, weβre going to simplify this expression first.
00:05:28.970 --> 00:05:34.700
First, weβre going to use the fact that the cot of π is the same as dividing by the tan of π.
00:05:34.960 --> 00:05:40.490
So, weβll remove the cot of π in our numerator and then square the tan of π in our denominator.
00:05:40.820 --> 00:05:45.280
Now, we want to simplify the csc of π divided by the sec of π.
00:05:45.410 --> 00:05:50.810
We know we can rewrite this as one over the sin of π divided by one over the cos of π.
00:05:51.110 --> 00:05:56.080
But we can then simplify this by multiplying the numerator and the denominator by the cos of π.
00:05:56.290 --> 00:06:01.650
In our denominator, we can cancel the cos of π divided by the cos of π to give us one.
00:06:01.940 --> 00:06:10.540
And in our numerator, we get the cos of π divided by the sin of π, but this is also equivalent to one divided by the tan of π.
00:06:10.810 --> 00:06:18.040
So, by using this, we can rewrite d two π¦ by dπ₯ squared as negative one divided by the tan cubed of π.
00:06:18.280 --> 00:06:23.600
And now, itβs easy to substitute our value of π equal to π by six into this expression.
00:06:23.840 --> 00:06:32.400
Doing this, we get d two π¦ by dπ₯ squared of π is equal to π by six is equal to negative one divided by the tan cubed of π by six.
00:06:32.670 --> 00:06:37.040
And if we evaluate this expression, we get negative three times the square root of three.
00:06:37.290 --> 00:06:43.350
So, weβve shown the second derivative of π¦ with respect to π₯ is negative when π is equal to π by six.
00:06:43.540 --> 00:06:48.150
Therefore, our curve must be concave downwards when π is equal to π by six.
00:06:48.330 --> 00:06:55.800
Therefore, given the parametric curve π₯ is equal to one plus the sec of π and π¦ is equal to one plus the tan of π.
00:06:55.980 --> 00:07:01.290
We were able to show that this curve was concave downwards when π was equal to π by six.